An examination of microstructure, microhardness and tribological properties of ceramic reinforced bronze matrix composite materials - Ada, H.; Türkmen, E.; Kaplan, Y.; Özçatalbaş, E.; Şatir, E. Y.; Aksöz, S. (National Library of Serbia, 2023)
In order to obtain better mechanical properties in a bronze alloy, it is important to produce new materials by adding reinforcements and to offer these materials to the industry. In this study, bronze matrix (Cu10Sn) materials were reinforced with boron carbide (B4C) and silicon carbide (SiC) ceramic materials by using the mechanical alloying method. New composite materials were produced by powder metallurgy method by adding ceramic reinforcement (B4C and SiC) at 1, 2, 4 and 8 weight ratios to Cu10Sn alloy, which is the main matrix material. The obtained composite materials examined in terms of structural, microhardness and wear resistance. Coefficient friction, specific wear rate and volume loss rates under 5N, 10N, and 15N loads were examined for the samples produced. When the applied microhardness and wear behaviors were examined, it was generally seen that the hardness and wear behaviors were improved with the added reinforcement ratios. In line with the examinations made, based on the hardness and wear processes applied to the materials consisting of the bronze matrix of the reinforcement material, it was observed that the most appropriate results were obtained from composite materials (Alloy 4 and Alloy 8), which contain 4% B4C and SiC reinforcement.
Keywords: Particle reinforced composites; Wear resistance; wear; Tribology; Composites material; Composite; Silicon carbide; TP1-1185; Weight ratios; Matrix composite; Wear; Powder metallurgy; microhardness.; Ceramic reinforcements; Boron carbide; composite; Bronze matrix; Chemical technology; Silicon carbide ceramic; Wear behaviors; Binary alloys; Mechanical alloying method; bronze; Wear of materials; powder metallurgy; Bronze; Tribological properties; Microstructures properties; Microhardness; Mechanical alloying; 8. Economic growth